The neurological symptoms of COVID-19 - Zandi, Michael (Henry Stewart Talks, 2020)
Diversity and incidence of neurological symptoms attributable to COVID-19, Mechanisms by which SARS-CoV-2 infection triggers neurological symptoms, Singularity of SARS-CoV-2, among coronaviruses, in triggering neurological symptoms, Therapeutic approaches to prevent or improve neurological symptoms, Incidence of psychiatric symptoms resulting from COVID-19 in a subset of patients, Relationship between neurological and psychiatric symptoms